Neuromodulatory effect of transcranial direct current stimulation on cue reactivity and craving in young adults with internet gaming disorder: an event-related potential study - Kim, Sung Nyun; Choi, Jung-Seok; Park, Minkyung; Yoo, So Young; Choi, Areum; Koo, Ja Wook; Kang, Ung Gu (Frontiers in Public Health, 2025)
ObjectiveThis study assessed the effects of transcranial direct current stimulation (tDCS) on cue reactivity and craving for game-related cues using event-related potentials (ERPs) in internet gaming disorder (IGD) patients.MethodsAt baseline, a series of game-related and neutral pictures were shown to both IGD and healthy controls (HCs) while ERPs were recorded. Late positive potentials (LPP) were used to investigate cue reactivity. During intervention, IGD patients received 10 sessions (two sessions/day for 5 consecutive days, 2 mA for 20 min/session) of tDCS to the left (anode stimulation) and right (cathode) dorsolateral prefrontal cortex. Subjectively assessed craving and LPP component was analyzed before stimulation and at the 1-month follow-up after tDCS in IGD.ResultsAt baseline, patients with IGD showed higher LPP amplitudes for game-related cues in the centro-parietal and parietal regions than HCs. After 10 sessions of tDCS, increased LPP amplitudes decreased significantly at 1-month follow-up., as well as subjective craving for gaming.ConclusionThese findings suggest that neurophysiological arousal in response to game-related cues in the IGD group could be modulated by the effects of tDCS. LPP was a significant neurophysiological marker of the neuroplastic response of cue reactivity underlying the therapeutic effect of tDCS on IGD. Based on the present findings, tDCS could be expanded to the treatment of other addictive disorders, including substance use disorder and behavioral addictions.